MISSING LINK TRADISI LISAN MENSTRUASI DI ERA MODERN: ANALISIS ISI FILM PADMAN 2018 - Siska Nur Apriyani; Inni Inayati Istiana; Moch Lukluil Maknun (Tambo: Journal of Manuscript and Oral Tradition, 2024)
Each oral tradition of a region is intended to hold noble meanings that are to be passed on to future generations. However, ideally the meaning of these traditions should be fluid and can be adapted to the context of the situation and conditions of the owner. One of the oral traditions that is collided with a modern context is found in the 2018 film Padman. The film criticizes traditions that alienate menstruating women by offering a rebuttal in the form of the discovery of sanitary napkins which medically and socially should be able to break this old tradition. Using a literature review approach, this article at least attempts to do the following things; 1) explore the initial meaning of the oral tradition of secluding women during menstruation in India which has become a myth and taboo; 2) criticism of oral traditions and their relevance to the current context. The results of this study can be stated: 1) the isolation of menstruating women in the film Pad Man is actually much lighter than the extreme traditions that occur in various worlds, and this myth is only part of the conflict in the film which spurs the main character to innovate until he succeeds thanks to his persistence 2) effort This study's interpretation of the meaning of the menstrual myth, which is not clearly stated in the film, can provide a fair position, that the myth actually contains a moral element of goodness in regulating the social system of society, at the same time that myths are not always ready for reform.